2017
DOI: 10.1002/ece3.3545
|View full text |Cite
|
Sign up to set email alerts
|

The effects of elevated CO2 (0.5%) on chloroplasts in the tetraploid black locust (Robinia pseudoacacia L.)

Abstract: Some ploidy plants demonstrate environmental stress tolerance. Tetraploid (4×) black locust (Robinia pseudoacacia L.) exhibits less chlorosis in response to high CO 2 than do the corresponding diploid (2×) plants of this species. We investigated the plant growth, anatomy, photosynthetic ability, chlorophyll (chl) fluorescence, and antioxidase activities in 2× and 4× black locusts cultivated under high CO 2 (0.5%). Elevated CO 2 (0.5%) induced a global decrease in the contents of total chl, chl a, and chl b in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
3
0
2
Order By: Relevance
“…Higher CO 2 concentrations will stimulate net photosynthesis by increasing CO 2 substrate availability for Rubisco, simultaneously suppressing photorespiration (Drake, Gonzàlez‐Meler, & Long, ). Thus, high CO 2 will increase photosynthesis, improving carbohydrate production (i.e., positive for growth and yield in crops), but will also cause several negative effects as carbon–nitrogen imbalance and/or decrease in the number of grana‐thylakoid structures (Cao, Jiang, Xu, Liu, & Meng, ; Teng et al, ). Although photorespiration induces a reduction in CO 2 assimilation, it provides protection of leaves during stress by dissipating excess reducing equivalents and energy, that is, adenosine triphosphate, NAD(P)H, and reduced ferredoxin (Voss, Sunil, Scheibe, & Raghavendra, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher CO 2 concentrations will stimulate net photosynthesis by increasing CO 2 substrate availability for Rubisco, simultaneously suppressing photorespiration (Drake, Gonzàlez‐Meler, & Long, ). Thus, high CO 2 will increase photosynthesis, improving carbohydrate production (i.e., positive for growth and yield in crops), but will also cause several negative effects as carbon–nitrogen imbalance and/or decrease in the number of grana‐thylakoid structures (Cao, Jiang, Xu, Liu, & Meng, ; Teng et al, ). Although photorespiration induces a reduction in CO 2 assimilation, it provides protection of leaves during stress by dissipating excess reducing equivalents and energy, that is, adenosine triphosphate, NAD(P)H, and reduced ferredoxin (Voss, Sunil, Scheibe, & Raghavendra, ).…”
Section: Introductionmentioning
confidence: 99%
“…negative effects as carbon-nitrogen imbalance and/or decrease in the number of grana-thylakoid structures (Cao, Jiang, Xu, Liu, & Meng, 2017;Teng et al, 2006). Although photorespiration induces a reduction in CO 2 assimilation, it provides protection of leaves during stress by dissipating excess reducing equivalents and energy, that is, adenosine triphosphate, NAD(P)H, and reduced ferredoxin (Voss, Sunil, Scheibe, & Raghavendra, 2013).…”
mentioning
confidence: 99%
“…It is worth noting that, in this study, triploid showed a higher chlorophyll fluorescence than diploid, which is supported by a previous study on triploid ‘Mantianxing’ [ 31 ]. Higher chlorophyll fluorescence was widely observed in another polyploid plant [ 61 ], even under stress conditions [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esse processo está relacionado às taxas de assimilação de CO 2 e o eCO 2 pode influenciar no metabolismo de carboidratos. As alterações fisiológicas podem aumentar a produção de carboidratos, influenciar no crescimento e o rendimento de espécies cultivadas (CAO et al, 2017). O elevado CO 2 influencia na eficiência fotossintética MORGAN et al, 2007;WANG et al, 2012) e geralmente aumenta a quantidade de carboidratos disponíveis na planta (ARENQUE et al, 2014;PALACIOS, 2017).…”
Section: Mudanças Climáticas E O Efeito Do Elevado Co 2 Na Vegetaçãounclassified
“…Os carboidratos solúveis em geral aumentam nas plantas submetidas à elevada concentração de CO 2 , levando a um acúmulo nas folhas (ARENQUE et al, 2014;PALACIOS, 2017). Esse acúmulo pode resultar em um aumento na taxa de crescimento e produtividade CAO et al, 2017).…”
Section: Introductionunclassified